Case Report: Cerebral venous sinus thrombosis in the setting of iron deficiency anemia and a high level of lipoprotein (a) in a child - Bustamante, Yomara Yarden; Seebeck, Ulrike; Bührlen, Martina; Overberg, David (Frontiers in Pediatrics, 2025)
Cerebral venous sinus thrombosis (CVST) is a rare but life-threatening condition among children. Several case reports have linked CVST formation to severe iron deficiency anemia (IDA). Iron deficiency anemia remains a public health problem, even in high-income countries. Among the thrombophilic factors accepted by some authors is an elevated lipoprotein (a). This is a case of a two-year-old girl with cerebral venous sinus thrombosis in the setting of IDA and high lipoprotein (a). These factors have been correlated with increased frequency in several clinical reports.